2020
DOI: 10.1186/s40337-020-00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders amongst Aboriginal and Torres Strait Islander Australians: a scoping review

Abstract: Background Aboriginal and Torres Strait Islander Australians (Indigenous Australians) have poorer mental health compared to other Australians. Yet, there is a lack of research into mental disorders among this population, especially for eating disorders (ED), which are amongst the most lethal and debilitating mental disorders. Aim We aimed to answer 2 questions: 1. What is the volume and content of literature on ED among Indigenous Australians? 2. Has a screening or diagnostic tool/instrument been developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…There is limited research on the experience of eating disorders in Aboriginal and Torres Strait Islander peoples. However, emerging research suggests that eating disorders are more common in Aboriginal and Torres Strait Islander adults and youth compared with non-Indigenous people [ 38 ].…”
Section: Contextmentioning
confidence: 99%
“…There is limited research on the experience of eating disorders in Aboriginal and Torres Strait Islander peoples. However, emerging research suggests that eating disorders are more common in Aboriginal and Torres Strait Islander adults and youth compared with non-Indigenous people [ 38 ].…”
Section: Contextmentioning
confidence: 99%
“…In interpreting the results of the current study, there are some limitations that should be considered. As there is variability in ED presentations between ethnic backgrounds ( Rodgers et al, 2018 ) and between White and Indigenous Australians ( Burt et al, 2020 ), it is notable that the majority of participants who completed the survey for the current study identified as White. In addition, the data gathered from gender diverse participants was excluded from the statistical analyses conducted in this study.…”
Section: Discussionmentioning
confidence: 98%
“…It is notable that the majority of participants who completed the survey for the current study identified as White. There is variability in eating disorder presentations between ethnic backgrounds [ 86 ] and between White and Indigenous Australians [ 87 ]. We also relied on self-report measures in this study, and had to omit some scales due to unacceptable internal consistency.…”
Section: Discussionmentioning
confidence: 99%